Adsorption and folding dynamics of MPER of HIV-1 gp41 in the presence of dpc micelle - Hartono, Yossa Dwi (2013)
Membrane-proximal ectodomain region (MPER) of HIV-1 gp41 is known to have several epitopes of monoclonal antibodies. It also plays an important role in the membrane fusion process that is well-evidenced, though not well-elucidated. There are also disputes over the true structure of MPER. In this study, MPER NMR structure in the presence of dodecylphosphatidylcholine micelle is used in the molecular dynamic simulation to elucidate structural dynamics and adsorption to model MPER interaction in a membrane environment. Polarized protein-specific charge derived from its NMR structure is found to better preserve the helical structure found in the NMR structure compared to AMBER03 calculation. The preserved helical structure also adsorb to the micelle using the hydrophobic side-chains, consistent to the NMR structure. Ab initio folding of MPER predicts a structure quite in well agreement with the NMR structure (RMSd 3.9 Å) and shows that the micelle plays a role in the folding process.